Organizational Culture, Work Ethos on Employees’ Motivation and Performance At UPT Surabaya Road – Bridge Management - Auliaillah Ilmi Rahadianto; Slamet Riyadi; Riyadi Nugroho (Indonesian Journal of Multidisciplinary Science, 2022)
Performance can be influenced by the encouragement or motivation of employees to be willing to work harder, work ethic in accordance with loyalty or a strong sense of love for the values and goals of the organization, and organizational culture that can trigger or stimulate employee performance to be better. Robbins and Judge (2015: 358) state that a strong culture will have a great influence on the behavior of its members because the high level of togetherness and intensity creates an internal climate of high behavioral control. The analysis data technique used in this research is a quantitative analysis using SEM (Structural Equation Modeling) model or Structural Equation Model with AMOS 23.0 program. The result of this research is the regression between organizational culture and work motivation, the CR value (Critical Ratio) is 5.720. The regression between organizational culture and employee performance has a CR (Critical Ratio) value of 2,508. Between work ethic and work motivation, the CR (Critical Ratio) value is 2,345. Between work ethic and employee performance, the CR (Critical Ratio) value is 1.961. Between work motivation and employee performance, the CR (Critical Ratio) value is 4.298.